2018
DOI: 10.1007/s12671-018-0982-4
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Training in UK Secondary Schools: a Multiple Case Study Approach to Identification of Cornerstones of Implementation

Abstract: This paper examined the facilitators and barriers to implementation of mindfulness training (MT) across seven secondary/high schools using a qualitative case study design. Schools varied in level of implementation. Within schools, head teachers, members of school senior leadership teams, and staff members involved in the implementation of MT were interviewed individually. In addition, focus groups were conducted with other members of school staff to capture a broad range of views and perspectives. Across the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 31 publications
4
62
1
3
Order By: Relevance
“…A study by Wilde et al (2019) interviewed senior leadership, school staff and mindfulness trainers at seven secondary schools in the process of implementing MT to understand their experiences of implementation [28]. This study found four main factors which affected the implementation of MT: having champions in the schools driving implementation forward, having resources and time to implement MT, there being a shared understanding of MT and why it is being introduced by school staff, and there being an understanding that implementation occurs through stages and takes time.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Wilde et al (2019) interviewed senior leadership, school staff and mindfulness trainers at seven secondary schools in the process of implementing MT to understand their experiences of implementation [28]. This study found four main factors which affected the implementation of MT: having champions in the schools driving implementation forward, having resources and time to implement MT, there being a shared understanding of MT and why it is being introduced by school staff, and there being an understanding that implementation occurs through stages and takes time.…”
Section: Introductionmentioning
confidence: 99%
“…This might indicate that positive outcomes are harder to improve on under this condition, but it needs to be confirmed and explained with more detail in future research. Only very recently have studies examined the implementation of MBIs in health [92] and education [93]. These studies have used an established theoretical framework to map the key contextual and facilitating factors that support implementation, with some overlap (e.g., the importance of "champions") and some differences (e.g., importance of clinical guidelines in health and "perceptions of mindfulness" in education).…”
Section: Discussionmentioning
confidence: 99%
“…Given the high workloads and time pressured roles of schoolteachers, is it likely that such a service could only ever be more fully embedded into the organisation and acknowledged as part of individual workers' roles with greater prioritisation from senior leaders than was evident here. Previous studies have reported that school level factors, which may include how far senior leaders are concerned about mental health, can interfere with the successful implementation of interventions aiming to support the mental health or staff or students [27][28][29]. Further research to understand how schools and senior leaders view teacher mental health in relation to the broader organisational priorities, and how to encourage a high level of buy-in for interventions to support teachers, is needed.…”
Section: Comparison With the Literaturementioning
confidence: 99%